Doctrine of Force Majeure in Civil Law Due to Customs Regulatory Intervention in Indonesian Bonded Zones - Erwin Erwin (Universitas Islam Sultan Agung, 2026)
This article aims to reconstruct the force majeure doctrine in Indonesian civil law to accommodate state regulatory intervention in customs within bonded zones. The classical force majeure doctrine under Articles 1244–1245 of the Indonesian Civil Code traditionally focuses on natural disasters and unforeseeable events, leaving regulatory interventions unaddressed. The urgency lies in increasing state regulatory changes in customs policies mandatory e-seals, transportation restrictions, expanded quarantine inspection, surveyor report obligations, and proposed reduction of domestic sales caps that disrupt contractual performance in export-oriented industries within bonded zones. The novelty is the